O szkolnictwie zawodowym Krakowa w zasobach archiwalnych Lwowa. Stan i perspektywa badań - Ślęczka, Ryszard (Biuletyn Historii Wychowania, 2023)
The paper focuses on research into vocational education in Krakow. The state of the art as well as the perspectives are presented. The main part provides a detailed analysis of the historical materials collected in Ukraine’s Central State Historical Archives in Lviv with enormous resources titled the National School Board. The achievements of the Polish sustem of education, specifically the development of vocational schools in Krakow, are presented in details based on these resources. A general overview shows the cognitive value of the specific collections (sets) in relation to one of the most important scientific and educational centres in Galicia in southern Poland.